Decorative Variety of Bebet Weave in the Sasak Ende Tribe in Central Lombok, Nusa Tenggara Barat - Jayadi, Jayadi; Nurliana, Andi; Tangsi, Tangsi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This research aims to (1) Describe the tools and materials used in weaving. (2) Describe bebet woven motifs in the Sasak tribe community. (3) Describing the classification of the use of bebet weaving in the Sasak tribe community. (4) Describing the supporting and inhibiting factors in the process of making bebet weaving. Data collection instruments using documentation, observation and interview techniques. Data obtained from observations, interviews and documentation were then re-analysed using qualitative descriptive analysis techniques. The results showed that the ornamental variety in the Sasak Ende Tribe of Central Lombok has its own characteristics and in the manufacturing process did not encounter significant difficulties. This research concludes that: The decorative motifs of bebet woven fabric produced by craftsmen in Ende hamlet include: (1) (2) traditional ornamental motifs that are modified (combining colours, lines, polygonal motif elements and geometric motifs). (3) The use of bebet in the Sasak Ende tribe can be used at nyongkolan or sorong serah aji kerame events, Gendang beleq (large drum) performances and Peresean events. (4) Supporting factors in the weaving activities of craftsmen in Ende hamlet include: equipment that is still available in homes, as a material to meet the needs of life because it can be of economic value. The inhibiting factors in weaving activities include: lack of skilled labour in transferring more diverse ornamental motifs on bebet cloth, limited capital and funds allocated to weaving activities that should continue to be developed.